2D Titania–Carbon Superlattices Vertically Encapsulated in 3D Hollow Carbon Nanospheres Embedded with 0D TiO2 Quantum Dots for Exceptional Sodium‐Ion Storage. (30th August 2019) - Xia, Qingbing; Lin, Zeheng; Lai, Weihong; Wang, Yongfei; Ma, Cheng; Yan, Zichao; Gu, Qinfen; Wei, Weifeng; Wang, Jia‐Zhao; Zhang, Zhiqiang; Liu, Hua Kun; Dou, Shi Xue; et al.
Abstract: Two‐dimensional (2D) superlattices offer promising technological opportunities in tuning the intercalation chemistry of metal ions. Now, well‐ordered 2D superlattices of monolayer titania and carbon with tunable interlayer‐spacing are synthesized by a molecularly mediated thermally induced approach. The 2D superlattices are vertically encapsulated in hollow carbon nanospheres, which are embedded with TiO2 quantum dots, forming a 0D‐2D‐3D multi‐dimensional architecture. The multi‐dimensional architecture with the 2D superlattices encapsulated inside exhibits a near zero‐strain characteristic and enriched electrochemical reactivity, achieving a highly efficient Na + storage performance with exceptional rate capability and superior long‐term cyclability. Abstract : Dimensionssprung : Geordnete, monolagige 2D‐Titandioxid‐Kohlenstoff‐Übergitter, die vertikal in hohlen Kohlenstoffnanokugeln verkapselt sind, wurden in TiO2 ‐Quantenpunkte eingebettet und bilden eine mehrdimensionale 0D‐2D‐3D‐Architektur. Aufgrund der Vorteile von 2D‐Übergittern und den synergistischen Effekten der einzelnen Bausteine zeigt die Architektur eine hohe Leistung für die Speicherung von Na + .